2021
DOI: 10.3390/foods10092015
|View full text |Cite
|
Sign up to set email alerts
|

Heat Treatment of Reishi Medicinal Mushroom (Ganoderma lingzhi) Basidiocarp Enhanced Its β-glucan Solubility, Antioxidant Capacity and Lactogenic Properties

Abstract: The effect of heat treatment on dried fruiting bodies of Reishi medicinal mushroom (Ganoderma lingzhi) is investigated. Control and samples treated for 20 min at temperatures of 70, 120, 150 and 180 °C were subjected for their free radical scavenging capacity, different glucans and total phenolic content determination. The growth rate of Escherichia coli and Lactobacillus casei supplemented with control and heat-treated samples is also investigated. The roasted mushroom samples at 150 °C and 180 °C showed the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 45 publications
0
10
0
1
Order By: Relevance
“…Mushrooms are important cornerstones in the search for natural antioxidants by scientists. In this context, studies on the antioxidant properties of mushrooms have gained in importance in recent years [ 24 , 25 ]. In the current study, the antioxidant properties of six Ganoderma species were determined by various chemical assays, and the results are shown in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Mushrooms are important cornerstones in the search for natural antioxidants by scientists. In this context, studies on the antioxidant properties of mushrooms have gained in importance in recent years [ 24 , 25 ]. In the current study, the antioxidant properties of six Ganoderma species were determined by various chemical assays, and the results are shown in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
“…As a result of the studies, it was observed that the antioxidant values increased due to the increase in concentration in general. Heat treatment may influence polyphenols, which are sensitive to high temperatures, resulting in a reduction in their content and antioxidant capacity (Kiss et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…1B). The partial degradation and conformation changes of β-glucan have been reported after heat treatment (26), hence these differences in SWEG and HWEG appear to have occurred due to the thermal energy of the extraction temperature.…”
Section: Comparison Of Chemical Properties Between Sweg and Hwegmentioning
confidence: 94%